Glenn Seaborg and Richard Nixon (1970)
Black and white photograph of Glenn Seaborg (1912-1999) standing next to President Richard M. Nixon (1913-1994). Nixon has inscribed the photograph with his signature and a note, "To Glenn Seaborg, with best wishes."
Keywords: Seaborg, Glenn T. (Glenn Theodore), 1912-1999; Nobel Prize winners; Nixon, Richard M. (Richard Milhous), 1913-1994